2010
DOI: 10.1128/jvi.00918-10
|View full text |Cite
|
Sign up to set email alerts
|

Interferons Accelerate Decay of Replication-Competent Nucleocapsids of Hepatitis B Virus

Abstract: Alpha interferon (IFN-␣) is an approved medication for chronic hepatitis B. Gamma interferon (IFN-␥) is a key mediator of host antiviral immunity against hepatitis B virus (HBV) infection in vivo.However, the molecular mechanism by which these antiviral cytokines suppress HBV replication remains elusive. Using an immortalized murine hepatocyte (AML12)-derived cell line supporting tetracycline-inducible HBV replication, we show in this report that both IFN-␣ and IFN-␥ efficiently reduce the amount of intracellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
116
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 113 publications
(120 citation statements)
references
References 56 publications
4
116
0
Order By: Relevance
“…However, we observed a slight increase in cytoplasmic capsid using DAKO (cytosolic Fab3105 stain: day 1 92 %, day 2 88 %, day 5 100 %; cytosolic DAKO stain: day 1 60 %, day 2 75 %, day 5 87 %). Such accumulation was expected for capsids, as their half-life (.24 h) in hepatoma cells is longer than that of monomeric core protein (Deres et al, 2003;Xu et al, 2010).…”
Section: Impact Of Viral Proteins On Core and Capsid Localizationmentioning
confidence: 87%
“…However, we observed a slight increase in cytoplasmic capsid using DAKO (cytosolic Fab3105 stain: day 1 92 %, day 2 88 %, day 5 100 %; cytosolic DAKO stain: day 1 60 %, day 2 75 %, day 5 87 %). Such accumulation was expected for capsids, as their half-life (.24 h) in hepatoma cells is longer than that of monomeric core protein (Deres et al, 2003;Xu et al, 2010).…”
Section: Impact Of Viral Proteins On Core and Capsid Localizationmentioning
confidence: 87%
“…In efforts to elucidate the antiviral mechanism of IFNs, it has been demonstrated that IFN-␣-and IFN-␥-induced antiviral responses either prevent the formation of pregenomic RNA (pgRNA)-containing capsids or promote the decay of replication-competent nucleocapsids in murine hepatocytes in culture and in transgenic mice in vivo (3,67,68). Recently, type III IFN (IFN-) has also been shown to inhibit HBV replication in cultured murine hepatocytes through a similar mechanism but with a weaker antiviral activity in transgenic mice (49,54).…”
Section: Interestingly Ido-mediated Tryptophan Deprivation Preferentmentioning
confidence: 99%
“…However, we did not observe any cytotoxic effect in HepG2 cultures transfected with a plasmid expressing IDO (data not shown). In addition, the fact that overexpression of IDO does not affect the steady-state level of HBV pgRNA, for which the half-life is less than 12 h in cell cultures (11,68,69), plus the lack of effect on the steady-state content of cellular proteins, such as TDO and ␤-actin (Fig. 4, bottom, lane 3), strongly suggested that expression of IDO in HepG2 cells did not significantly affect the host cellular transcription and translation machinery but preferentially inhibited HBV protein and DNA biosynthesis.…”
Section: Ifn-␣ and Ifn-␥ Inhibit Hbv Replication In Human Hepatocyte-mentioning
confidence: 99%
See 1 more Smart Citation
“…ISG modulation results in an antiviral response in target cells aimed at limiting both viral replication and spreading. IFN-α has been reported to inhibit HBV replication through a variety of mechanisms, including a block of RNA-containing core particle formation, an accelerated decay of replication-competent core particles, and degradation of the pgRNA (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%